2014
DOI: 10.1182/blood-2014-01-548800
|View full text |Cite
|
Sign up to set email alerts
|

PRIMA-1Met induces myeloma cell death independent of p53 by impairing the GSH/ROS balance

Abstract: Key Points• Myeloma cells are highly sensitive to PRIMA-1 Met , independent of p53.• PRIMA-1Met induces myeloma cell death by impairing GSH/ROS balance.The aim of this study was to assess the efficiency of p53 reactivation and induction of massive apoptosis (PRIMA-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
155
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(171 citation statements)
references
References 40 publications
11
155
0
2
Order By: Relevance
“…Taken together, our findings suggest that PK11007 and other thiol-modifying compounds, such as PRIMA, MIRA, and STIMA, despite alkylating and stabilizing the p53 protein, exert their antitumor function not only via reactivating p53 but also via other cellular mechanisms, such as increase of cellular ROS to toxic levels and activation of the UPR (33). This finding would also explain the seemingly contradictory reports that PRIMA-1, MIRA-1, and STIMA-1 induce cell death also in cell lines with DNA contact mutants that cannot be rescued by simple protein stabilization (12,11,14).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Taken together, our findings suggest that PK11007 and other thiol-modifying compounds, such as PRIMA, MIRA, and STIMA, despite alkylating and stabilizing the p53 protein, exert their antitumor function not only via reactivating p53 but also via other cellular mechanisms, such as increase of cellular ROS to toxic levels and activation of the UPR (33). This finding would also explain the seemingly contradictory reports that PRIMA-1, MIRA-1, and STIMA-1 induce cell death also in cell lines with DNA contact mutants that cannot be rescued by simple protein stabilization (12,11,14).…”
Section: Discussionmentioning
confidence: 65%
“…The biological effects of APR-246 may not be directly dependent on the p53 status but rather on the perturbation of the intracellular GSH/ROS balance and the respective cellular context (31)(32)(33). To test whether PK11007 also increases ROS levels, we incubated NUGC-3, NUGC-4, HUH-6, HUH-7, and MKN1 cells with PK11007 for 2 h and stained the cells with CellROX Deep Red dye, which exhibits a strong fluorescent signal upon oxidation by ROS.…”
Section: Pk11007 Induces Ros Especially In Mutant P53mentioning
confidence: 99%
“…However, several studies have suggested that APR-246 may also exert p53-independent effects. These include generating ROS,12 13 upregulating p7311 and suppressing c-Myc expression 11. Additionally, some investigators have even asserted that APR-246 may act entirely through p53-independent pathways in some tumour cells 11 12.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have also suggested that APR-246 may exert additional effects through p53-independent mechanisms 11–13. These include generating reactive oxygen species (ROS) by antagonising the glutathione and thioredoxin reductase 1 pathway,12 13 activating p63, p73 and promyelocytic leukaemia tumour suppressor proteins,11 14 15 and suppressing the c-Myc oncogene 11…”
Section: Introductionmentioning
confidence: 99%
“…Downloaded by [University of Western Ontario] at 14:50 11 April 2015highlighting the significance of ROS production in PRIMA-1Met-induced cell death26 ; thus it would be interesting to analyze the oxidative stress pathways in PRIMA-1Met-treated WM cells in future studies.…”
mentioning
confidence: 99%